A Role for Peroxisome Proliferator-Activated Receptors in the Immunopathology of Schistosomiasis? - Barrie J. Anthony; Jeremy T. Allen; Yuesheng S. Li; Donald P. McManus (PPAR Research)
Peroxisome proliferator-activated receptors (PPARs) have been demonstrated to have a role in immune regulation. In general, they are anti-inflammatory and promote Th2 type responses, and they are associated with the alternative activation of macrophages. Interestingly, helminth infections, such as the schistosome blood flukes that cause schistosomiasis, are characterised by a Th2 response and the accumulation of alternative activated macrophages. This would suggest that at some level, PPARs could have a role in the modulation of the immune response in schistosomiasis. This paper discusses possible areas where PPARs could have a role in this disease.